Tennessee Williams' The glass menagerie - Williams, Tennessee 1911-1983; Barry, John 1933-2011 (Image Entertainment, 2002)
A strong willed woman attempts to impose her shattered dreams into the life and personality of her shy, reclusive daughter.
Orig.: USA 1973
Enth. performer theatre and film credits ; image gallery
Keywords: Young men -- Drama; Saint Louis (Mo.) -- Drama; Feature films; Film adaptations